Pellicle modification with natural bioproducts: Influence on tooth color under erosive conditions. (15th July 2022) - Mailart, Mariane Cintra; Berli, Pavel Claudio; Borges, Alessandra Bühler; Yilmaz, Burak; Baumann, Tommy; Carvalho, Thiago Saads
Abstract: Salivary pellicle was modified with bioproducts and we assessed the change in tooth color and the protection of enamel to erosion. Human enamel specimens were assigned to one of three solutions: grape seed extract or black tea (bioproducts), or deionized water (negative control); after which one half the specimens underwent erosive challenges. The specimens underwent 15 cycles involving salivary pellicle formation (10 min, 37°C), incubation in solution (2 min, 25°C), subsequent pellicle formation (90 min, 37°C). Half of the specimens was kept in a humid chamber and the other half was submitted to erosion (2 min, 1% citric acid). After 15 such cycles, the pellicle was removed. Tooth color and the surface reflection intensity were assessed after every five cycles and after pellicle removal. For non‐eroded specimens, the exposure to bioproducts promoted significantly greater color change than the deionized water, with increases in yellow appearance. After pellicle removal, the color was similar in all non‐eroded specimens. The bioproducts increased the surface reflection intensity over cycles. For the erosion‐exposed specimens, erosion itself resulted in color change. Black tea and deionized water resulted in increased yellow appearance. Exposure to the bioproducts resulted in higher relative surface reflection intensity values over time, but only grape seed extract resulted in higher relative surface reflection intensity value at the time of pellicle removal. The bioproducts caused transient staining effect, which was reduced after pellicle removal. For enamel submitted to erosion, grape seed extract resulted in less color change and better protection of enamel against erosion than black tea or water.